Shelving dan Disorientasi Pengelolaan Jajaran Koleksi (Analisis terhadap Persoalan yang mengemuka dan Tawaran Solusinya) - Umar Falahul Alam (UIN Sumatera Utara, 2016)
Shelving is arranging library collections on the shelfes. This activity is very important to controll the collection and has role in the process of information retrieval. But nowdays the shelving it self still has some issues, first is a clerical job, so the job is considered not professional, and second is a main key of the process of retrieval of information / documents. The solution is to set up shelving employees who have professional competenceies in one side, and the other hand is that the need for rationalization with the number of personnel available. This step is the way to determine or make sure that the retrieval of information / documents can run well, without disrupting the work of expert librarians who have the other tasks of librarianship.